(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study aims to analyze the changes in some psychophysiological indicators before and after working days in medical staff of a military hospital in order to propose measures to improve work efficiency. Research methods: Cross-sectional descriptive with volunteers who are 205 staff members of 10 departments over a period of 4 months from December 2024 to March 2025. Results: Stress index WSS increased (p = 0.41), the Schulte concentration time index increased from 24.81 ± 3.10 seconds to 32.38 ± 5.15 seconds (p = 0.001), the SAN S emotional index decreased from 5.75 ± 0.17 to 4.50 ± 0.35 (p < 0.001), the SAN A activity index decreased from 6.02 ± 0.31 to 5.05 ± 0.35 (p < 0.001), the SAN N index decreased from 6.01 ± 0.31 to 5.03 ± 0.32 (p < 0.001). In particular, the stress index was high in the group of nurses and medical staff in departments A2, B1, B9. At the same time, the 3 SAN indices during the day changed in all departments but remained at an average level, the biggest change was in departments A2, B1, B9. That shows the level of work stress in large departments, however, medical staff tried to complete the work in a good psychological state. The respiratory physiological indices Stanghe and Ghenche changed after the working day statistically significant (p < 0.01). Conclusion: Research on the changes in psychophysiological indices in medical staff of military hospitals before and after the working day is the basis for developing a plan to assign and perform professional tasks effectively.